Kecemasan Remaja: Faktor-faktor Risiko Berdasarkan Model Ekologi Sosial - Ni Made Padma Batiari; Budiharto Budiharto; Tri Suratmi (INSAN Jurnal Psikologi dan Kesehatan Mental, 2022)
Emotional disorders can affect the overall health of adolescents. One frequent emotional disorder among adolescents is anxiety disorders. The fact that many factors play roles in the development of anxiety disorders in adolescents signifies the importance to investigate these factors among adolescents aged 14–17 years in Denpasar City. This study used a quantitative approach with a cross-sectional design and an analytical survey method. The results showed that out of 370 adolescents, 133 (35.9%) suffered from severe to extreme anxiety and other 125 (33.8%) experienced mild to moderate anxiety. History of any chronic disease, sleep quality, authoritarian parenting style, permissive parenting style, and family harmony were found to be associated with anxiety. Of these, sleep quality was the most predictive. Hence, it is necessary for the Health Department in Denpasar City, schools and parents to come together and raise awareness about the importance of sleep quality for adolescents.